(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
The article analyzes the qualitative changes that have occurred in Uzbekistan’s cooperation with Kazakhstan, Kyrgyzstan, Tajikistan, and Turkmenistan in the field of tourism in 2017–2026. Regional openness, simplification of border procedures, restoration of transport links, the idea of a common tourist space, cross-border and thematic routes, digitalization, and cooperation with international organizations are highlighted as key areas. The impact of the pandemic, existing institutional challenges, and prospects until 2026 are also assessed using a historical-comparative approach.